Analysis of Relationship between Three Dimensions of Quality, User Satisfaction, and E-Learning Usage of Binus Online Learning - Yosep, Yosep (CommIT (Communication and Information Technology) Journal, 2015)
Information technology has  affected  various sectors including the education sector. In the sector, information technology has brought us long distance  education,  which  relies  heavily  on  the  use   of e-learning management system. In Indonesia, Bina Nusantara University is the first and foremost long distance  education  institution.  The  institution  has  been developing and using an e-learning management system for a number of years. This work intends to evaluate to which extent the system is able to enhance e-learning experiences. We adopted the DeLone and McLean’s Information System success model and empirically measured the relation between the aspects of system quality, information quality, service quality, user satisfaction, and net benefits. From a population of the size 311 students, we have collected 149 responses using questionnaires by randomly selecting the participating students. The responses were used to establish a multi-variate regression model where the relationships were established. The model suggested that information quality, system quality, and service quality had positive impacts on user satisfaction with the p-values of 0.014, 0.014, and 0.000 respectively. In addition, the study also found that user satisfaction was strongly and positively affected by the net  benefits.